Electrochemical study the corrosion behaviour of carbon steel in mortars under compressive and tensile stresses. (February 2016) - Feng, Xingguo; Lu, Xiangyu; Zuo, Yu; Zhuang, Ning; Chen, Da
Highlights: The intensified corrosion of the rebar results primarily from the stress-induced degradation of the concrete/rebar interface. For the same magnitude of stress, the rebar in the compressed mortar is more severely corroded than its counterpart in the tensile mortar. Micro-cracks in the mortars form along directions perpendicular to the applied tensile stress; compressive stresses result in the formation of de-bonding zones on the mortar/rebar interface. ABSTRACT: The influence of compressive and tensile stresses on the corrosion behaviour of the rebar in mortars was investigated. The corrosion of the rebar intensified with increasing magnitude of the stress. Results of electrochemical impedance spectroscopy and the observed corrosion state indicated that the stress-induced corrosion of the rebar resulted mainly from degradation of the concrete/rebar interface. For the same magnitude of stress, the rebar in the compressed sample was more severely corroded than that in the tensile sample. In addition, modes were proposed to illustrate the different failure patterns of the concrete/rebar interface, owing to the action of the stresses.